Ecofeminism in Djaïli Amadou Amal’s Cœur du Sahel: An Exploration of Gendered Dimensions of Climate Change and Environmental Degradation - Ebruphiyo Mamomo Ekanem (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
The relationship between environmental hazards and the subjugation of women is a major area of reflection in ecofeminism, a movement that links the exploitation of nature to the oppression of the feminine gender. Ecofeminism critiques the patriarchal association of women with nature, which has historically been used to justify the exploitation of both. This article examines ecofeminism in Djaïli Amadou Amal’s Cœur du Sahel (2020), with particular focus on the dimensions of climate change and environmental degradation as they relate to female subjugation. Viewed through the perspective of ecofeminism, which connects the domination of nature with the oppression of women, the study investigates how Amal’s novel portrays the interconnected oppression of women and the environment within the Sahelian context. The analysis highlights how drought, soil erosion, water scarcity, and natural resource decay intensify male dominance, disproportionately affecting women and girls. Females suffer the physical, emotional, and socio-economic burdens of environmental crises: forced migration, food scarcity, early marriage, and restricted access to education. Therefore, the study argues that Amal’s narrative positions women not only as victims of ecological and social injustice but also as agents of resilience and survival. The novel reveals the structural inequalities that link environmental degradation to gender-based marginalization. The article argues that Cœur du Sahel offers a powerful literary articulation of ecofeminist concerns, stressing the urgent need to address climate change through gender-sensitive approaches. Thus, the analysis concludes that integrating gender-sensitive approaches into climate policy is essential for achieving environmental sustainability and social justice.